Gambaran Program Kesehatan pada Dinas Pencegah Pemadam Kebakaran di Kota Medan - Afifah, Adinda; Rifdah, Annisa Aisy; Ansari, Cindi; Derina, Derina; Herawaty, Desy; Amira, Farah; Nabila, Febri; Utari, Luthfiyah; Shafa, Natasya; Rahmalila, Nindy; Nurwana, Rena; Aulia, Tasya; Chaniago, Tessya; Hastuty, Widya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The Medan City Fire Department, commonly known as Damkar or PMK, is an organization made up of people or troops who are tasked with extinguishing fires, conducting rescues, and handling disasters or other incidents. The Medan City Fire Department is one of the agencies prioritized to ensure the safety of its employees. The purpose of this article is a descriptive analysis of the medical programs carried out at the Medan City Fire Department. This research uses a qualitative method consisting of primary and secondary data. The number of informants is 1 person. The results of this study found that before the Covid-19 pandemic, there were several health programs implemented at the Fire Prevention Department. The conclusion of this study is that there are still some challenges related to the health programs implemented.